2018
DOI: 10.5897/jaerd2017.0919
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder farmers experiences of climate variability and change on pineapple production in Ghana: Examining adaptation strategies for improved production

Abstract: Climate variability and change presents enormous risk to agricultural production globally due to the impacts on yields. While global scholarship on climate change impacts and adaptation measures on agriculture has been well-documented, little is known about climate and pineapple production. This study examined smallholder pineapple farmers experiences of climate variability and change on production, as well as ranked adaptation options using data from both primary and secondary sources. The primary data consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…April to July is the major planting period in the pineapple sub-sector. This agrees with a study by Williams et al [18] who found that pineapple farmers in Ghana plant their materials mainly from March to July. In some areas such as the Nsawam-Adoagyiri, and the Akuapim South Districts, suckers and/or slips planting spans from March to December.…”
Section: Table 3 Planting Periods For Pineapple In the Study Areasupporting
confidence: 93%
“…April to July is the major planting period in the pineapple sub-sector. This agrees with a study by Williams et al [18] who found that pineapple farmers in Ghana plant their materials mainly from March to July. In some areas such as the Nsawam-Adoagyiri, and the Akuapim South Districts, suckers and/or slips planting spans from March to December.…”
Section: Table 3 Planting Periods For Pineapple In the Study Areasupporting
confidence: 93%
“…Timely planting, use of improved cultivars, variation in planting dates, multiple cropping are some adaptation practices adopted at farm level (Ndamani and Watanabe 2015). In Ghana, several adaptation strategies such as intensification of irrigation, shift from on-farm to off-farm jobs, changes in cultivation practices, seasonal migration, on-farm fertiliser application and insurance against drought effects have been recorded (Williams et al 2018c(Williams et al , 2019Bawakyillenuo et al 2016). Others include shifts in planting period, planting drought tolerant crop varieties, planting on elevated ridges, irrigation of crops with water from streams and tree planting.…”
Section: Adaptation Measures Employed At the Local Levelmentioning
confidence: 99%
“…However, these studies failed in addressing the impacts of climatic risks on smallholder livestock farmers, farmers' perception and strategies livestock farmers used to adapt to the risks in Eastern Amhara Region. Adaptation is not generic rather it is location and time specific or contextualized to the available resources, needs, cultural values and perception [ [20]], [51] and its effectiveness depends on local institutions and socioeconomic setting of a particular location [ [2]], [ [44]].…”
Section: Climatic Risk Adaptation Strategies By Smallholder Livestockmentioning
confidence: 99%